2022
DOI: 10.1097/mjt.0000000000001531
|View full text |Cite
|
Sign up to set email alerts
|

Solifenacin Treatment After Intradetrusor Injections With Botulinum Toxin in Patients With Neurogenic Detrusor Overactivity

Abstract: Background:Neurogenic detrusor overactivity (NDO) is treated with antimuscarinics as first-line treatment. For patients with contraindications or unresponsive, intradetrusor injections with botulinum toxin (BoNT) are a safe and effective but expensive option.Study Question:Our study evaluated whether adding solifenacin to the intradetrusor injection of BoNT A could boost the effect of BoNT in patients with NDO due to multiple sclerosis or spinal cord injury refractory to antimuscarinics alone and/or lead to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These three separate scores added together result in an overall score between 0 and 21. A lower score indicates a better outcome for symptom severity: mild (1-5), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18) and very severe (19)(20)(21) [26]. A similar postoperative ICIQ-UI SF questionnaire was used at follow-up visits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These three separate scores added together result in an overall score between 0 and 21. A lower score indicates a better outcome for symptom severity: mild (1-5), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18) and very severe (19)(20)(21) [26]. A similar postoperative ICIQ-UI SF questionnaire was used at follow-up visits.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment for MUI is still challenging and often involves a combination of surgery and medication, depending on the primary complaint [ 1 ]. Weight loss, bladder training and pelvic floor muscle development are all known to help patients regardless of the type of UI [ 16 ]. Weight-loss therapies have been observed to lessen the frequency of UI in obese women [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, intravesical onabotulinumtoxin A injection has the potential to improve the urgency symptom for UUI in DHIC [11]. The concurrent administration of intravesical onabotulinumtoxin A injection and solifenacin could alleviate the DO symptom and extend the time between subsequent reinjections [12]. In addition, sacral neuromodulation has the potential to improve UUI and address compromised detrusor contractile function.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with botulinum toxin could be a reasonable alternative to neural stimulation and has only limited side effects, generally related to the surgical procedure [17]. Recently, Ciofu et al revealed that the response to botulinum toxin in patients with neurogenic detrusor overactivity can be improved by additional treatment with solifenacin, a selective antagonist of the M3 muscarinic receptor [18]. Therefore, we decided to analyze the possible association between the ADRB3:rs4994 polymorphism and response at three months to a single intra-detrusor injection of botulinum toxin-A in Polish women with overactive bladder.…”
Section: Introductionmentioning
confidence: 99%